The Effects of Temperature on Growth and Reproduction of Aquatic Snails - Henry Van der Schalie; Elmer G. Berry (Hello World!, 1973)
Mollusks, like other animals cited, are very sensitive to ambient temperatures. Even small changes are shown to be important in their influence on the environmental area affected. Studies are encouraged to determine the effects of temperature changes well in advance of projected developments such as the use of natural waters for cooling reactors, for cooling reactors, e.g.- 'improvements' that could adversely affect the flora and fauna of the surrounding region.